Variations of the seismic b-value along the Dead Sea transform - Sharon, Matty; Kurzon, Ittai; Wetzler, Nadav; Sagy, Amir; Marco, Shmuel; Ben-Avraham, Zvi (Frontiers in Earth Science, 2022)
The frequency-magnitude distribution follows the Gutenberg-Richter empirical law, in which the scaling between small and large earthquakes is represented by the b-value. Laboratory experiments have shown that the b-value is related to fault mechanics with an inverse dependency to the differential stress, as was also inferred from observational datasets through relations with earthquake depth and style of faulting. In this study, we aim to obtain a better understanding of the geological structure and tectonics along the Dead Sea transform (DST), by examining relations of the b-value to three source parameters: the earthquake depth, the seismic moment release, and the predominant style of faulting. We analyse a regional earthquake catalogue of ~20,300 earthquakes that were recorded between 1983–2020 in a regional rectangle between latitudes 27.5°𝑁−35.5°𝑁 and longitudes 32°𝐸−38°𝐸. We convert the duration magnitudes, Md, to moment magnitudes, Mw, applying a new regional empirical relation, by that achieving a consistent magnitude type for the entire catalogue. Exploring the variations in the b-value for several regions along and near the DST, we find that the b-value increases from 0.93 to 1.19 as the dominant style of faulting changes from almost pure strike-slip, along the DST, to normal faulting at the Galilee, northern Israel. Focusing on the DST, our temporal analysis shows an inverse correlation between the b-value and the seismic moment release, whereas the spatial variations are more complex, showing combined dependencies on seismogenic depth and seismic moment release. We also identify seismic gaps that might be related to locking and/or creeping of sections along the DST and should be considered for hazard assessment. Furthermore, we observe a northward decreasing trend of the b-value along the DST, which we associate to an increase of the differential stress due to structural variations, from more extensional deformation in the south to more compressional deformation in the north.